Microwave-assisted synthesis and formation mechanism of fluorescent carbon dots from starch - Hisahiko Shibata; Mina Abe; Kazuya Sato; Koji Uwai; Kiyotaka Tokuraku; Toshifumi Iimori (Carbohydrate Polymer Technologies and Applications, 2022)
We report the synthesis of fluorescent carbon dots (CDs) via the microwave (MW)-assisted hydrothermal treatment of starch in an aqueous phosphoric acid solution. CDs emitting blue, orange, and green fluorescence in different solvents were obtained. The fluorescence quantum yield of the CDs emitting blue fluorescence is 30%, which is comparable to those of semiconductor quantum dots. The formation of the CDs under MW irradiation was monitored using a spectroscopic approach. The formation of blue-fluorescent CDs began at an early stage of the reaction. Subsequently, the CDs underwent aggregation. The aggregations were effectively extracted to the toluene layer by liquid−liquid extraction, and they emitted orange fluorescence in toluene and green fluorescence in water. The formation of the aggregates was followed by a steep increase in the yield of the CDs that emit blue fluorescence. MW heating for a certain duration was required to increase the yield of the blue-fluorescent CDs.